AKSES DAN JAMINAN PERLINDUNGAN PEREMPUAN PENGGUNA INTERNET: Suatu Kajian Akses dan Kebebasan Berekspresi Perempuan dalam Internet - Marta, Andri; Hermawan, Dedy; Ikram, Ikram (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study aims to describe women's access and freedom of expression in using internet technology related to their need for information, protection of women victims of Gender- Based Sexual Violence (KSBG) online, and legal services, as well as developing networks free from violence and discrimination. The next goal is to get an idea of how far state agencies, law enforcement officials and private authorities in internet governance fulfill the protection of women's rights to access and freedom of expression, as well as the protection of victims of KSBG. This study used qualitative research methods with a phenomenological approach through in-depth interviews and documentation. Research data was obtained from 7 (seven) informants, namely activists of the DAMAR Association, Nawala, APJII, the PPA Unit and Police Cyber Crime, and Kominfo. The results show that internet governance related to the protection of women's rights to access and freedom of expression, as well as the protection of victims of Gender-Based Sexual Violence (KSBG) online is an issue that is still growing, has not been managed properly, and still requires further attention from the government, as well as the private sector. Although there are many regulations governing access and freedom of expression in cyberspace, both international, national, regional, they have not been able to guarantee the fulfillment of the Right to Access and Freedom of Expression, especially related to online gender-based violence and health services, law, and assistance for victims of Gender-Based Sexual Violence (KSBG). Many online KSBG victims do not report because of shame, stigma, or uncertainty in the handling of cases by the authorities. Women's greater access to the internet is essential to achieve digital inclusivity and women's empowerment. In order for women to have equal access and protection to internet use, free from violence and discrimination, a comprehensive effort involving various stakeholders is needed